2022
DOI: 10.1109/te.2021.3123889
|View full text |Cite
|
Sign up to set email alerts
|

Software Engineering Education Knowledge Versus Industrial Needs

Abstract: Contribution: Determine and analyze the gap between software practitioners' education outlined in the 2014 IEEE/ACM Software Engineering Education Knowledge (SEEK) and industrial needs pointed by Wikipedia articles referenced in Stack Overflow (SO) posts.Background: Previous work has uncovered deficiencies in the coverage of computer fundamentals, people skills, software processes, and human-computer interaction, suggesting rebalancing.Research Questions: 1) To what extent are developers' needs, in terms of Wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Studies have identified deficiencies in the coverage of computer fundamentals, people skills, software processes, and HCI in software engineering education. Addressing these gaps is essential for aligning educational curricula with the evolving needs of the software industry [23].…”
Section: Education and Industrial Needs In Software Developmentmentioning
confidence: 99%
“…Studies have identified deficiencies in the coverage of computer fundamentals, people skills, software processes, and HCI in software engineering education. Addressing these gaps is essential for aligning educational curricula with the evolving needs of the software industry [23].…”
Section: Education and Industrial Needs In Software Developmentmentioning
confidence: 99%
“…Literature [19] provided an industrial internship instruction model for undergraduate industrial engineering education in public universities, combining qualitative and quantitative methods, and verified that the internship model developed students' engineering skills and abilities. Literature [20] sought the needs of developers during the development of the computer industry based on the content of Wikipedia and covered the effect of the coverage of industrial education through the calculation of knowledge units. Literature [21] provided an effective method of industry-education integration for vocational education related to the semiconductor industry and constructed an intelligent simulation training system for actual production.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main causes of software bugs is from the specification [1] [2]. As software specification gathered from the user's needs is mostly written in common natural languages in the Software Requirements Specification (SRS) document [3][4] [5], this leads unstructured requirements to be ambiguous and misunderstood by software developers [4][6] [7]. Furthermore, in system and user acceptance testing, test cases are generated from the SRS.…”
Section: Introductionmentioning
confidence: 99%